Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the inequality [tex]\( -6(4 - x) \leq -4(x + 1) \)[/tex], we will go through a step-by-step process of simplification and solving.
1. Distribute the constants inside the parentheses:
[tex]\[ -6(4 - x) \leq -4(x + 1) \][/tex]
Expanding both sides:
[tex]\[ -6 \cdot 4 + 6 \cdot x \leq -4 \cdot x - 4 \cdot 1 \][/tex]
Simplifying further:
[tex]\[ -24 + 6x \leq -4x - 4 \][/tex]
2. Combine the [tex]\(x\)[/tex] terms on one side and constants on the other side:
Add [tex]\(4x\)[/tex] to both sides to get all [tex]\(x\)[/tex] terms on the left:
[tex]\[ -24 + 6x + 4x \leq -4x + 4x - 4 \][/tex]
Simplifying this:
[tex]\[ -24 + 10x \leq -4 \][/tex]
3. Isolate the [tex]\(x\)[/tex] term by eliminating constants from the left side:
Add 24 to both sides:
[tex]\[ -24 + 24 + 10x \leq -4 + 24 \][/tex]
Simplifying this:
[tex]\[ 10x \leq 20 \][/tex]
4. Solve for [tex]\(x\)[/tex] by dividing both sides by 10:
[tex]\[ 10x \leq 20 \][/tex]
Dividing both sides by 10:
[tex]\[ x \leq \frac{20}{10} \][/tex]
Simplifying:
[tex]\[ x \leq 2 \][/tex]
Thus, the solution to the inequality [tex]\( -6(4 - x) \leq -4(x + 1) \)[/tex] is [tex]\( x \leq 2 \)[/tex].
Therefore, the correct answer is:
C. [tex]\( x \leq 2 \)[/tex]
1. Distribute the constants inside the parentheses:
[tex]\[ -6(4 - x) \leq -4(x + 1) \][/tex]
Expanding both sides:
[tex]\[ -6 \cdot 4 + 6 \cdot x \leq -4 \cdot x - 4 \cdot 1 \][/tex]
Simplifying further:
[tex]\[ -24 + 6x \leq -4x - 4 \][/tex]
2. Combine the [tex]\(x\)[/tex] terms on one side and constants on the other side:
Add [tex]\(4x\)[/tex] to both sides to get all [tex]\(x\)[/tex] terms on the left:
[tex]\[ -24 + 6x + 4x \leq -4x + 4x - 4 \][/tex]
Simplifying this:
[tex]\[ -24 + 10x \leq -4 \][/tex]
3. Isolate the [tex]\(x\)[/tex] term by eliminating constants from the left side:
Add 24 to both sides:
[tex]\[ -24 + 24 + 10x \leq -4 + 24 \][/tex]
Simplifying this:
[tex]\[ 10x \leq 20 \][/tex]
4. Solve for [tex]\(x\)[/tex] by dividing both sides by 10:
[tex]\[ 10x \leq 20 \][/tex]
Dividing both sides by 10:
[tex]\[ x \leq \frac{20}{10} \][/tex]
Simplifying:
[tex]\[ x \leq 2 \][/tex]
Thus, the solution to the inequality [tex]\( -6(4 - x) \leq -4(x + 1) \)[/tex] is [tex]\( x \leq 2 \)[/tex].
Therefore, the correct answer is:
C. [tex]\( x \leq 2 \)[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.